2016
DOI: 10.1091/mbc.e14-08-1332
|View full text |Cite
|
Sign up to set email alerts
|

Kif26b controls endothelial cell polarity through the Dishevelled/Daam1-dependent planar cell polarity–signaling pathway

Abstract: An atypical kinesin, Kif26b, is identified as a signaling effector of the Wnt PCP under Daam1 signaling. Molecular evidence shows that it interacts with Dvl3/Daam1. Kif26b is involved in endothelial microtubule network stabilization and has a crucial role together with the Dvl3/Daam1 complex in establishing endothelial cell polarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Previous investigators have reported that KIF26B localises to microtubules in human endothelial cells. 33 Our data confirm that KIF26B has at least a partial co-localisation with the cytoskeleton in MSCs ( Figure 3F). In silico analysis 34 of a published RNASeq dataset in an in vivo model of ectopic bone formation using human foetal MSCs from an independent study 35 also demonstrated KIF26B induction during osteogenesis ( Figure 3G).…”
Section: Variation Within the Casc20 Locus Is Associated With Ho Suscsupporting
confidence: 82%
“…Previous investigators have reported that KIF26B localises to microtubules in human endothelial cells. 33 Our data confirm that KIF26B has at least a partial co-localisation with the cytoskeleton in MSCs ( Figure 3F). In silico analysis 34 of a published RNASeq dataset in an in vivo model of ectopic bone formation using human foetal MSCs from an independent study 35 also demonstrated KIF26B induction during osteogenesis ( Figure 3G).…”
Section: Variation Within the Casc20 Locus Is Associated With Ho Suscsupporting
confidence: 82%
“…Sst , Kif26b , Mab21l2 , and Lamp5 mRNAs are also highly enriched and expressed in C‐neurons (Figure h). Sst encodes the hormone Somatostatin (Patel, ); Kif26b encodes a kinesin that regulates cell polarity (Guillabert‐Gourgues et al, ; Marikawa, Fujita, & Alarcon, ); Mab21l2 encodes a nuclear protein that interacts with the BMP4 signaling pathway and has been implicated in neural tube formation and eye morphogenesis (Baldessari, Badaloni, Longhi, Zappavigna, & Consalez, ; Huang, ); Lamp5 encodes a lysosome‐associated membrane protein implicated in GABAergic neurotransmission (Tiveron et al, ). In situ hybridization for these mRNAs in brachial spinal cord transverse sections from E11.5 Robo3 Cre/+ ; ROSA26 LSL‐tdTomato/+ embryos confirmed expression in various subgroups of C‐neurons and revealed additional sites of expression (Figure a–h).…”
Section: Resultsmentioning
confidence: 99%
“…This could change the balance from a symmetric to an asymmetric MT network and is crucial for proper polarization of cells (Burute et al, 2017). In contrast, in epithelial cells, endothelial cells and mouse airway cilia, regulatory proteins ensure that MTs grow mainly from the apical membrane, rather than from the centrosome (Feldman and Priess, 2012;Vladar et al, 2012;Guillabert-Gourgues et al, 2016;Toya et al, 2016). The result is that MTs grow in parallel bundles instead of a radial conformation, which leads to different transport directions (Fig.…”
Section: Cytoskeleton-based Cell Polaritymentioning
confidence: 99%